USING WORD WALL TECHNIQUE TOWARDS THE STUDENTS’ VOCABULARY MASTERY AT THE ELEVENTH GRADE OF VOCATIONAL HIGH SCHOOL STUDENTS - Rina Puji Utami (Dharma Pendidikan, 2020)
This research paper investigates the effectiveness of word wall technique on the students’ vocabulary mastery at the eleventh grade of SMK NU Pace in the academic year of 2019/2020. The objectives of the research are (1) To find the students’ vocabulary mastery before using word wall technique, (2) To find the students’ vocabulary mastery after using word wall technique, (3) To analyze the significant difference before and after using word wall technique of students’ vocabulary mastery. The reseach is Pre-Experimental with one group pre-test post-test. the reseach was done in SMK NU Pace in acadaemic year of 2019-2020, by using the population whole class XI with the total 248 students, while the sample is used by the reseacher is the class XI-I involving number of class is 28 students. The technique of sampling is using purposive sampling. The collecting data used test. The technique of analysis data used to analyze the data in this reseach is statistical analysis data t-test. Based on the result of the test, students show the score – average pre-test 48,78 and post-test 72,64. The category is good. Based on the results of analysis level significance in d.b 5% is 27 value table is 1,703 and value of t-test is 13,007. It can be concluded as follow: ttest > ttable so, Ho is rejected and Ha is accepted. So that, “There is significant difference before and after using word wall technique of students’ vocabulary mastery at the Eleventh Grade Students’ of SMK NU Pace in the 2019/2020 Academic Year”. Contributing the significant result of using word wall technique towards vocabulary mastery is discussed in this paper.